Isolation and Identification of Bacteria from Hawked Suya Meat Sold within Katsina Metropolis (Sahel Journal of Life Sciences FUDMA, 2024)
The consumption of suya meat is rising significantly due to the product's growing demand.  Perishable foods like meat and meat products such as soya meats are susceptible to deterioration by microorganisms. The research was conducted to ascertain the microbiological quality of suya meat sold in the Katsina metropolis. 25 samples were purchased from five different suya meat vendors. The bacteria from the suya meat products were isolated and characterized using standard microbiological techniques. Results of the investigations revealed the presence of Salmonella species, Bacillus species, Staphylococcus species, and Escherichia coli.  The most predominant isolate is Escherichia coli with the percentage of occurrence of 24.13% while Salmonella and Staphylococcus species were the least occurring with 17.4% each. The antibiotic resistance profile of isolated bacteria showed that the majority of the bacteria were resistant to Gentamycin, Streptomycin, Amoxicillin, Penicillin, and Cefoperazone. Results of the investigation revealed that the handling techniques used by vendors and the unhygienic conditions in which suya meat are sold may be the reason for such microbial contamination. Good hygienic practices should be adopted in the processing of such meat products.